A study on maternal and perinatal outcome in premature rupture of membranes at term - Surayapalem, Sailaja; Cooly, Vijayalakshmi; Salicheemala, Bhuvaneswari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Premature rupture of membranes is defined as rupture of foetal membranes before the onset of labour. Management of cases of PROM still remains as one of the most difficult and controversial problems in obstetrics. PROM can cause maternal complications like chorioamnionitis, increased operative procedures, puerperal sepsis and neonatal morbidity and mortality. The present study is undertaken to study the labour outcome, maternal morbidity and perinatal morbidity and mortality in term PROM. Methods: 200 Cases of spontaneous rupture of membranes with gestational age >37 weeks with confirmed PROM by a speculum examination were selected. A detailed history was taken, and gestational age confirmed, general, systemic and obstetric examinations were done. Parameters of maternal and foetal well being were recorded. All study groups received prophylactic antibiotics. Single pelvic examination done, and maternal vitals recorded fourth hourly. All the data was analyzed and statistical significance was calculated using Chi-square test. Results: PROM was common in age group of 20-24 years (35%) with mean age of 22.6 years and SD of 2.8 years, and common in primigravida. Majority of women were admitted within six hours of PROM (41.5%) and Mean duration of induction to delivery interval was 12.9 hours. The mean duration between PROM to delivery was 20.2 hours which was statistically significant. Cesarean sections were more among primigravidas. Failure to progress was the common indication. Maternal morbidity was significant (17.5%). No maternal mortality in the study. Perinatal mortality was 1.5%. Birth asphyxia was the commonest cause. Perinatal morbidity was seen in 26%. Escherichia coli was common organism found in cervical swab culture. Conclusions: In present study, majority was primigravidas and the most common age group was 20-24 years belonging to low socioeconomic status. Maternal morbidity and neonatal morbidity was associated with increased duration of PROM to delivery and infection of the female genital tract with pathogens. Hence an appropriate and accurate diagnosis of PROM is essential for favorable outcome in pregnancy.